Use of pregnancy personalised follow-up in case of maternal social vulnerability to reduce prematurity and neonatal morbidity - Simon Crequit; Gregory Bierry; Perbellini Maria; Sakina Bouali; Adelaïde Dupre La Tour; Naima Sgihouar; Bruno Renevier (BMC, 2023)
Abstract Background Social deprivation is a major risk factor of adverse pregnancy outcomes. Yet, there is few studies evaluating interventions aiming at reducing the impact of social vulnerability on pregnancy outcomes. Objective To compare pregnancy outcomes between patients that received personalized pregnancy follow-up (PPFU) to address social vulnerability versus standard care. Methods Retrospective comparative cohort in a single institution between 2020 and 2021. A total of 3958 women with social vulnerability that delivered a singleton after 14 gestational weeks were included, within which 686 patients had a PPFU. Social vulnerability was defined by the presence of at least one of the following characteristics: social isolation, poor or insecure housing conditions, no work-related household income, and absence of standard health insurance (these four variables were combined as a social deprivation index (SDI)), recent immigration (< 12 month), interpersonal violence during pregnancy, being handicaped or minor, addiction during pregnancy. Maternal characteristics and pregnancy outcomes were compared between patients that received PPFU versus standard care. The associations between poor pregnancy outcomes (premature birth before 37 gestational weeks (GW), premature birth before 34 GW, small for gestational age (SGA) and PPFU were tested using multivariate logistic regression and propensity score matching. Results After adjustment on SDI, maternal age, parity, body mass index, maternal origin and both high medical and obstetrical risk level before pregnancy, PPFU was an independent protective factor of premature birth before 37 gestational weeks (GW) (aOR = 0.63, 95%CI[0.46-0.86]). The result was similar for premature birth before 34 GW (aOR = 0.53, 95%CI [0.34-0.79]). There was no association between PPFU and SGA (aOR = 1.06, 95%CI [0.86 - 1.30]). Propensity score adjusted (PSa) OR for PPFU using the same variables unveiled similar results, PSaOR = 0.63, 95%CI[0.46-0.86] for premature birth before 37 GW, PSaOR = 0.52, 95%CI [0.34-0.78] for premature birth before 34 GW and PSaOR = 1.07, 95%CI [0.86 - 1.33] for SGA. Conclusions This work suggests that PPFU improves pregnancy outcomes and emphasizes that the detection of social vulnerability during pregnancy is a major health issue.